Point-of-care biosensor for stroke biomarker detection - Lu, Alicia YiTian (2018)
Stroke is the second highest cause of death globally. Stroke occurs when there is a sudden disruption of blood-flow to the brain, resulting in a reduction of oxygen cells to the brain cells and subsequent loss of control of the body. To prevent irreparable neuronal death, blood-flow must be supplied immediately. Stroke patients are currently assessed largely based on clinical evaluation and is supported by neuroimaging methods. However, emerging data point to the potential use of blood-derived biomarkers in aiding clinical decision-making especially in the diagnosis of ischemic stroke, triaging patients for acute reperfusion therapies, and in informing stroke mechanisms and prognosis. As treatment is time-sensitive, there has been an increase in demand to innovate on how to best transmit individualized information to the incident site. The Point-Of-Care-Test (POCT) is the current approach taken to solve this issue. It is portable, user-friendly and has proven efficient in reducing the time-to-treatment. It is able to group different stroke subtypes and help improve patient’s conditions. This report tested proof-of-concept for the use of novel PVA films inside stack-pad in order to stop sample flow for a required time, allowing for further developmental testing of the device with actual samples and target stroke biomarkers.